Improving fuzzy traffic controller for multilane-multiple intersection - Che Soh, Azura; Khalid, Marzuki; Marhaban, Mohammad Hamiruce; Yusuf, Rubiyah (IEEE, 2009)
This paper presents a fuzzy traffic controller for controlling a multilane-multiple traffic intersection in urban city environment. The developed controller applied to the model is based on the cooperation and distributed mechanisms with the neighbors' intersection. The phase sequence and phase length extension are used in decision making to provide efficient and more optimal traffic control. The input variables are normalized and the proposed fuzzy traffic controller is suitable to be used to any case study without modification to the controller modules. The simulation illustrates that the fuzzy traffic controller proposed in this study show a remarkable improvement over the existing fuzzy traffic controller without input normalization.